2020
DOI: 10.1021/acsomega.9b04452
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum-Waste-Derived High-Surface Area KOH-Activated Porous Carbon for Highly Efficient Methylene Blue and Pb(II) Removal

Abstract: With the development of the environment and human society, the removal of metal ions and dyes in wastewater treatment remains an urgent problem to solve. In this work, two biomass carbon adsorbents were synthesized by a KOH activation and carbonization route using sorghum stem and root as carbon precursors. In comparison with the samples without KOH activation, the pore structure of the KOH-activated carbon has been dramatically improved. The findings show that the specific surface areas of the adsorbents by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…SVFs showed two characteristic peaks at 16.1° and 21.9°, and the strong peak at 21.9° indicated the hydrogen bond interaction between the cellulose chains. The CMTs and ZnO/CMT exhibited a broad diffraction peak at 22.4°, which corresponds to the (002) graphite plane. , Remarkably, the diffraction peak at 22.4° of CMTs was wider than that of ZnO/CMT, indicating that the degree of graphitization of CMTs was lower . The diffraction peaks of ZnO/CMT appearing at 31.77°, 34.42°, 36.25°, 47.54°, 56.60°, and 62.86° correspond to the (100), (002), (101), (102), (110), and (103) planes, respectively, which matched the wurtzite phases of hexagonal ZnO .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…SVFs showed two characteristic peaks at 16.1° and 21.9°, and the strong peak at 21.9° indicated the hydrogen bond interaction between the cellulose chains. The CMTs and ZnO/CMT exhibited a broad diffraction peak at 22.4°, which corresponds to the (002) graphite plane. , Remarkably, the diffraction peak at 22.4° of CMTs was wider than that of ZnO/CMT, indicating that the degree of graphitization of CMTs was lower . The diffraction peaks of ZnO/CMT appearing at 31.77°, 34.42°, 36.25°, 47.54°, 56.60°, and 62.86° correspond to the (100), (002), (101), (102), (110), and (103) planes, respectively, which matched the wurtzite phases of hexagonal ZnO .…”
Section: Resultsmentioning
confidence: 97%
“…A peak at 2841 cm –1 was identified as the 2D band, and the appearance of 2D peaks was expected to make CMTs and ZnO/CMT have good electrical conductivity. ,, The relative intensity ratio of I D / I G revealed the degree of graphitization, and the I D / I G values of CMTs and ZnO/CMT were 0.72 and 0.69, respectively. This indicated that the graphitization degree of ZnO/CMT was higher. , As shown by the FTIR spectra in Figure i, the intensity of the peak at 3442 cm –1 corresponding to the stretching vibration of O–H is strongest for the SVFs, indicating a great number of O–H groups on the SVFs. This is consistent with the fact that the SVFs are made of cellulose with rich hydroxy groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectra showed that two intensive bands at about 1350 cm –1 (D band) and 1580 cm –1 (G band) corresponded to the defective carbon structure and the ordered structure of carbon with the sp 2 electronic configuration, respectively. 42 , 43 Usually, the degree of graphitization was estimated via the intensity ratio of the G/D band ( I G / I D ). Meanwhile, the value of I G / I D could also be influenced by the nitrogen content.…”
Section: Results and Discussionmentioning
confidence: 99%